Neurofilaments in heart failure-depicting the brain-heart axis. (3rd October 2022) - Prausmueller, S; Wurm, R; Ponleitner, M; Spinka, G; Weidenhammer, A; Arfsten, H; Bartko, P E; Goliasch, G; Huelsmann, M; Pavo, N
Abstract: Introduction: Experimental studies have fueled theoretical concerns about neurocognitive side effects of the angiotensin-receptor-neprilysin-inhibitor (ARNi) sacubitril/valsartan as neprilysin is not only involved in the degradation of vasoactive peptides, but also in the degradation of amyloid-β in the brain. To date, no study could demonstrate cognition- and dementia-related adverse effects following neprilysin-inhibition. Recent advances in blood-based tests made it feasible to precisely measure the concentration of neurofilament light chain in plasma (sNfL).sNfl has been found to be altered in neurodegenerative disease, making it a potential biomarker for screening and early detection of cognitive impairment. This study investigated the association of sNfL levels with the severity of disease and prognosis in heart failure with reduced ejection fraction (HFrEF) and explored the response of sNfL levels to the initiation of ARNi. Methods: HFrEF patients were prospectively enrolled and clinically followed-up.sNfL levels were measured by a single-molecule array assay. The association of sNfL with heart failure (HF) severity and outcome was assessed. The discriminatory power of sNFL was assessed using Harrell's C-statistic and was compared to NT-proBNP. In a subset of 47 patients, sNfL levels were determined before the initiation of ARNi (baseline), 3±2 months (short-term) and 12±3 months (long-term) after. Results: A total of 177 HFrEF patients were included into the study. Median age was 61 years (IQR: 51–72) and 75% of patients were male. Median sNfL levels were 26.2 pg/ml (IQR: 14.1–43.8).sNfL concentration was significantly associated with HF severity reflected by NT-proBNP (rs=0.361, p<0.001) and NYHA class (p<0.001) (Figure 1A). Thirty-one (17.5%) patients died during a median follow-up time of 2.8 years (IQR: 2.3–3.3). Increased sNfL concentration was indicative for worse overall survival even after adjustment for age, sex, kidney function and NT-proBNP [adj. HR for ln[sNfL]: 1.78 (95% CI: 1.13–2.80, p=0.012] (Figure 1B). In terms of discriminatory accuracy, sNfl was comparable with NT-proBNP (C-index: 0.75 [CI: 0.67–0.83] vs. 0.71 [CI: 0.63–0.80], p=0.299). Regarding the effect of ARNi-therapy no significant change in sNfL was observed at short- and long-term follow-up (26.0 pg/ml [IQR: 15.1–51.4] vs. 31.5 pg/ml [IQR: 15.8–51.3]; vs. 31.3 pg/ml [IQR: 15.5–54.0], p>0.05 for all) (Figure 2). Conclusions: This study suggests that sNFL is a high performing marker to predict outcome in HFrEF independent of NT-proBNP. NEP-inhibition by ARNi does not seem to reasonably influence sNfL levels. The nature of sNfL release is uncertain. As sNfL is assumed to be specific for axonal injury, sNfL increase in HFrEF may be driven by hypoperfusion due to fixed peripheral vasoconstriction characteristic for more severe disease states. Whether sNfL levels are able to aid screening and early therapy of neurocognitive decline in HFrEF has to be elucidated in further studies. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Austrian Society of Cardiology - Research Grant